Multi-disciplinary trends in artificial intelligence : 12th International Conference, MIWAI 2018, Hanoi, Vietnam, November 18-20, 2018, Proceedings /: 12th International Conference, MIWAI 2018, Hanoi, Vietnam, November 18-20, 2018, Proceedings. (2018) - Unknown
No abstract available